2019
DOI: 10.1111/hel.12569
|View full text |Cite
|
Sign up to set email alerts
|

Twice daily short‐message‐based re‐education could improve Helicobacter pylori eradication rate in young population: A prospective randomized controlled study

Abstract: Background To investigate the effects of twice daily short‐message‐based re‐education (SMRE) before taking medicine for Helicobacter pylori (H pylori) eradication. Materials and Methods Treatment‐naive patients with H pylori infection were prescribed 14‐day quadruple regimen consisting of lansoprazole 30 mg, colloidal bismuth pectin 200 mg, amoxicillin 1000 mg, and clarithromycin 500 mg twice daily. Patients were randomly allocated to SMRE group or control group. Patients in control group received oral and wri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(87 citation statements)
references
References 27 publications
(45 reference statements)
0
82
0
Order By: Relevance
“…Two recent large randomized controlled trials from China demonstrated that the use of an interactive smartphone medical application 20 and text-based reminders 21 during treatment improved adherence to primary therapy. These adjunctive systems are worthy of further investigation in the United States for refractory H pylori infection and would provide information on which approaches might be more effective in certain populations compared with others; for example, based on characteristics such as age, race and ethnicity, educational level, access, and language.…”
Section: Nonadherencementioning
confidence: 99%
“…Two recent large randomized controlled trials from China demonstrated that the use of an interactive smartphone medical application 20 and text-based reminders 21 during treatment improved adherence to primary therapy. These adjunctive systems are worthy of further investigation in the United States for refractory H pylori infection and would provide information on which approaches might be more effective in certain populations compared with others; for example, based on characteristics such as age, race and ethnicity, educational level, access, and language.…”
Section: Nonadherencementioning
confidence: 99%
“…It is, therefore, worthwhile to explore methods to improve the eradication rate. A previous study reported that patient compliance is an indispensable factor influencing treatment results[ 21 ]. In addition, high-dose PPI and amoxicillin dual therapy could decrease the use of unnecessary antibiotics, which is a promising alternative approach[ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…72 In Japan, a study looked at an enhanced compliance program by getting pharmacists to provide instruction for patients being prescribed eradication therapy but found modest, if any, benefit with 91% achievement in the intervention group compared to 88% in the group getting vonoprazan without special pharmacist instruction with a slight benefit in cost-effectiveness ratio (223 vs 224). 75 74 In China, it was shown that sending patients short phone text messages could increase compliance and improve adherence to therapy.…”
Section: Adheren Cementioning
confidence: 99%
“…74 In China, it was shown that sending patients short phone text messages could increase compliance and improve adherence to therapy. 75…”
Section: Adheren Cementioning
confidence: 99%